L’entreprise de Giotto - Daphné de Luca (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The comparative study of several big wooden crosses painted by Giotto allowed to deepen the work organization in the Middle Ages’ workshop. This analysis found several analogies of execution between the works, by demonstrating that the production of these masterpieces was subordinated to certain codified rules, pre-established by the workshop’s master, a really skilful business manager of the Middle Ages.